If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6x + -8) + -8(2 + 3x) = -32 Reorder the terms: 8(-8 + 6x) + -8(2 + 3x) = -32 (-8 * 8 + 6x * 8) + -8(2 + 3x) = -32 (-64 + 48x) + -8(2 + 3x) = -32 -64 + 48x + (2 * -8 + 3x * -8) = -32 -64 + 48x + (-16 + -24x) = -32 Reorder the terms: -64 + -16 + 48x + -24x = -32 Combine like terms: -64 + -16 = -80 -80 + 48x + -24x = -32 Combine like terms: 48x + -24x = 24x -80 + 24x = -32 Solving -80 + 24x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '80' to each side of the equation. -80 + 80 + 24x = -32 + 80 Combine like terms: -80 + 80 = 0 0 + 24x = -32 + 80 24x = -32 + 80 Combine like terms: -32 + 80 = 48 24x = 48 Divide each side by '24'. x = 2 Simplifying x = 2
| 5(10+6m)= | | -(6+4x)-8(8x-3)=-50 | | -7+5(2r-6)=-107 | | 5(3x+9)(5x-15)=0 | | (x-4)(x+1)=14 | | e^9x=3 | | 5(1+3b)+7(7-3b)=30 | | -5p+-4(-p+4)= | | 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 |